EFEKTIVITAS MODEL PEMBELAJARAN PJBL TERINTEGRASI STEAM UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KREATIF DAN HASIL BELAJAR IPAS SISWA KELAS V SEKOLAH DASAR - Bayu Prastiwi, Arlinda; Yulianto, Sigit (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The low level of students' creative thinking skills and learning outcomes can be influenced by the lack of teacher innovation in the IPAS learning process. This study aims to determine the effectiveness of the STEAM-integrated PjBL learning model in improving creative thinking skills and learning outcomes of grade V students of IPAS-content elementary schools. This research uses a quantitative experimental method using a quasi-experimental design of the nonequivalent control group type. This study used purpose sampling in sampling with a total of 44 students. Data collection techniques through post-tests using multiple choice questions and essays, questionnaires, interviews, and documentation. The hypothesis test results show that the sig. (2-tailed) value is smaller than α, namely 0.000 <0.05, which shows that the use of the STEAM-integrated PjBL learning model has a significant effect in improving students' creative thinking skills and learning outcomes. Based on this, it can be concluded that there is an influence on students' creative thinking skills and learning outcomes through the STEAM-integrated PjBL learning model in grade V elementary school on the IPAS content.